Palliative Care for SARS-CoV-2 Patients in the Intensive Care Unit: A Comprehensive Study - Marilia Alves Furtado; Vitória Pessoa Nogueira; Maria Clara Passos Araújo; Virna Ribeiro Feitosa Cestari; Vera Lúcia Mendes de Paula Pessoa (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To comprehend the multiprofessional actions regarding palliative care for patients in the Intensive Care Unit affected by SARS-CoV-2. Methods: A comprehensive qualitative study conducted with 31 professionals from the Intensive Care Units of a university hospital, based on the Theory of Peaceful End of Life. Results: The analysis of the discourse led to the identification of two categories: "Multidisciplinary actions to promote comfort at the end of life" and "Palliative care during the pandemic period and the promotion of emotional and spiritual comfort." Final Considerations: It became evident that local administration needs to invest in measures that reduce barriers to the implementation of palliative care during times of crisis. Understanding the discourse highlighted that non-specialized professionals can provide basic palliative care appropriately, without diminishing the importance and necessity of the presence of palliative care specialists in various hospital areas.